LDL sialic acid content in patients with coronary artery disease - Ruelland, A.; Gallou, G.; Legras, B.; Paillard, F.; Cloarec, L. (Clinica chimica acta, 1993)
Low density lipoproteins (LDL) are considered to be the most atherogenic of lipoproteins. These LDL can be modified and oxidative modifications are now well known. In addition, other atherogenic modifications of LDL exist, such as desialylation. In the present study sialic acid content was determined in LDL preparations obtained from patients with coronary artery disease (CAD+) and compared with that of healthy subjects and patients without coronary heart disease (CAD-). The sialic acid concentration was found to be statistically lower ( P < 0.05) in the LDL of CAD+ patients (11.6 ± 2.7 gmg/mg of protein) than in the LDL of controls (16.5 ± 5.6 gmg/mg of protein) or in the LDL of CAD- patients (15.3 ± 3.8 gmg/mg of protein). In subgroups of CAD+ patients divided according to the severity of the disease, no statistically significant difference was observed in LDL sialic acid content. This work confirms the presence of desialylated LDL in the sera of patients with atheroma.